An efficient method to produce segregating populations in quinoa (Chenopodium quinoa). (3rd November 2020) - Emrani, Nazgol; Hasler, Mario; Patiranage, Dilan S. R.; Nathaly, Maldonado‐Taipe; Rey, Elodie; Jung, Christian
Abstract: Quinoa offers a promising alternative for staple food, considering its outstanding nutritional value and tolerance to abiotic stresses. To develop breeding programmes in quinoa, a reliable crossing method for increasing the genetic variation is required. In the following study, we aimed to develop segregating populations in quinoa. We tested the efficiency of three different crossing methods (hand emasculation, warm water emasculation and no emasculation). Moreover we developed a two‐stage selection strategy based on morphological traits and molecular markers for the selection of hybrid plants. We reported hand emasculation to be the most efficient crossing method, followed by warm water emasculation and no emasculation. Our results demonstrated that crosses in quinoa can be successfully performed, despite its complicated flower structure and high self‐pollination rate. Additionally, we developed 30 segregating populations from crosses between accessions of different origins with varying phylogenetic relationship, which offers a promising perspective for quinoa breeding programmes in the future.